Reaksi Pasar Terhadap Pelemahan Nilai Rupiah Pada Nilai Tukar US Dollar - Putra, R. Egi Pradnya; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The sampling method used was purposive sampling with a total sample of 39 companies from the LQ45 stock index for the period February-July 2018. The data analysis technique used paired sample t-test with a significance level of 5% on normal distributed data and the Wilcoxon test on data not normal distribution. This study produces a significant difference between the abnormal return and trading volume activity before and after the weakening of the rupiah value on the US Dollar exchange rate against the LQ45 company stock listed on the IDX. The results of this study support the theory of market efficiency where the market responds to incoming information, and how that information can further influence the movement of securities prices towards new equilibrium prices. Keywords : Market reaction, event study, weakening rupiah value, abnormal return, trading volume activity.